1999
DOI: 10.1055/s-0037-1614485
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K Intake and Sensitivity to Warfarin in Patients Consuming Regular Diets

Abstract: The effect of dietary vitamin K intake on warfarin sensitivity is known only from case reports and few small clinical studies. We followed 50 patients commencing warfarin and consuming their regular diets (for 8 weeks) to study this relationship. A one-week recall dietary questionnaire was completed at weeks 2 and 8. Daily intake of nutrients and vitamin K was calculated from standard tables. Warfarin sensitivity index (WSI) was defined as final INR/final warfarin dose (mg/day/m 2 of body surface area) (week 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 16 publications
(12 reference statements)
4
57
1
Order By: Relevance
“…Alterations in dietary intake of vitamin K can have a significant effect on anticoagulation response to oral anticoagulants; increases in the dietary intake of vitamin K are associated with significant reductions in anticoagulation response, 6,9,[12][13][14][15] whereas the opposite causes warfarin sensitivity. 6,12 Earlier we showed that in patients with stable control of anticoagulation, for every 100-g increase in vitamin K intake in the previous 4 days, INR falls by 0.2, 16 further exemplifying the relationships between dietary vitamin K and anticoagulation response.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in dietary intake of vitamin K can have a significant effect on anticoagulation response to oral anticoagulants; increases in the dietary intake of vitamin K are associated with significant reductions in anticoagulation response, 6,9,[12][13][14][15] whereas the opposite causes warfarin sensitivity. 6,12 Earlier we showed that in patients with stable control of anticoagulation, for every 100-g increase in vitamin K intake in the previous 4 days, INR falls by 0.2, 16 further exemplifying the relationships between dietary vitamin K and anticoagulation response.…”
Section: Discussionmentioning
confidence: 99%
“…26 Patients who consume large amount of dietary vitamin K also require significantly higher warfarin doses to prevent subtherapeutic dosing. 27 Additionally, medications that impact warfarin pharmacokinetics or pharmacodynamics can also dramatically alter dose requirement. 28 For example, drug inhibition of the warfarin metabolizing enzyme CYP2C9 can alter warfarin pharmacokinetics, resulting in a decreased warfarin dose requirement.…”
Section: Genetic and Clinical Factorsmentioning
confidence: 99%
“…4 A high dietary intake of vitamin K leads to a higher dose requirement, while old age is associated with lower doses. [8][9][10][11] Diseases that increase the sensitivity to warfarin include liver dysfunction impairing the synthesis of coagulation proteins, hypermetabolic states that increase the clearance of coagulation factors and congestive heart failure that alters the distribution of warfarin. 3,6,11 Warfarin is highly bound to serum albumin, which in combination with its extensive cytochrome P450 (CYP) metabolism and narrow therapeutic range makes warfarin susceptible to drug interactions.…”
Section: Introductionmentioning
confidence: 99%